Svetlana Aleksievič, Tempo di seconda mano. La vita in Russia dopo il crollo del comunismo (Altre Modernità, 2019)
Svetlana Aleksievič, Tempo di seconda mano. La vita in Russia dopo il crollo del comunismo (Milano, Bompiani, 2018, 777 pp. ISBN 978-88-452-9753-3)di Francesca Volpi